PROFIL REPRESENTASI VISUAL MAHASISWA PADA MATA KULIAH GEOMETRI - Istikaanah, Najmah; Prayito, Muhammad (Universitas Jenderal Soedirman, 2019)
ABSTRACT. The specific purpose of this study is to determine the profile of visual representation of students in geometry courses. This research is a qualitative research. The data collection method is done through documentation, observation, learning achievement tests and questionnaires. The results showed that the ability of visual representation of 1st semester students at mathematics education was still low. This is reviewed in the student's ability to answer learning achievement test at geometry courses.Keywords: learning achievement ,visual representation, geometry. ABSTRAK. Tujuan khusus penelitian ini adalah mengetahui profile representasi visual mahasiswa pada mata kuliah Geometri. Penelitian ini merupakan penelitian kualitatif. Metode pengambilan data dilakukan melalui dokumentasi, observasi, tes hasil belajar dan angket. Hasil penelitian menunjukkan bahwa kemampuan representasi visual mahasiswa semester 1 program studi pendidikan matematika masih rendah. Hal tersebut ditinjau pada kemampuan mahasiswa untuk menjawab soal tes hasil belajar mata kuliah Geometri. Kata Kunci: Hasil Belajar, Representasi Visual, Geometri.